Students’ Attitudes towards Reading Saudi Printed and Electronic Saudi Newspapers - Abdalrazig, Abdalhalim Musa Yagoub (Dirasat: Human and Social Sciences, 2023)
Objectives: The purpose of this study is to determine the attitudes of Saudi students regarding reading printed and electronic newspapers as well as the reasons behind their decisions. Additionally, due to variations in the commitment of each type of newspaper is to this crucial aspect of professional practice, the credibility and professionalism issues in printed and electronic newspapers often lead to the spread of rumors and inaccurate information. Methods: The data for the study were collected using a questionnaire, which was sent to a sample of 360 undergraduate and graduate students at the Department of Media at King Faisal University, KSA. Results: There was no correlation between student’s attitudes towards reading electronic newspapers and the future of print journalism. Furthermore, there was no correlation between student’s attitudes towards reading electronic newspapers and news credibility. It was found that electronic newspapers have lower credibility than printed newspapers, primarily due to the absence of institutions relying on censorship through gatekeepers, as observed in press institutions. Conclusion: In comparison to printed newspapers, the study found that many electronic newspapers lack professionalism and disseminate misleading news.